PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN DAN SIKAP IBU MENYUSUI TENTANG ASI EKSKLUSIF - Febriyeni Febriyeni (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract : Mother's Milk (ASI) is a baby's main requirement, exclusive breastfeeding demands good knowledge about exclusive breastfeeding. Health education about exclusive breastfeeding is an important factor that can influence maternal knowledge about exclusive breastfeeding. This study aims to determine the effect of health education using audio visual media on the knowledge and attitudes of breastfeeding mothers about exclusive breastfeeding in the Kolok health center Sawahlunto in 2018. This type of research is pre-experiment with pre post test design approach. The population of this study were all breastfeeding mothers who had infants aged